The Shadow of Crime: Impact on Prison Experiences and Recidivism Tendency - Roza Süleymanoğlu (Journal of Economy Culture and Society)
This study aims to understand the impact of prison experiences on recidivism. A phenomenological approach was adopted, total of 15 people were interviewed and a semi-structured interview form was used. Network connections and snowball sampling were used to reach the participants. For this reason, we first attempted to understand the meanings attributed by the participants to concepts such as crime, criminality, and guilt. Prison experiences included daily functioning, adaptation processes and communication with inmates and staff. The impact of the participants’ prison experiences on their post-release lives and recidivism was analyzed. It was observed that the process of adaptation to prison differed according to the types of crimes, length of sentence and experiences. Prison experiences are not a reason for reoffending in themselves. Individual differences, familial reasons, criminal motivation and external factors related to post-prison conditions such as labeling and poverty, also play key roles in recidivism. The effect of the criminal subculture in prison on recidivism has also been observed. Prison experiences can trigger psychological problems, and after release, factors related to stigmatization, poverty, housing, employment, financial income, exclusion and official supervision make it difficult to adapt to social life.